Super capacitor case and super capacitor having the same

CN123004136APending Publication Date: 2026-10-30SHANGHAI YONGMING ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611218799.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有超级电容器非金属外壳依然存在耐电解液腐蚀性、抗冲击性、散热性比较差的问题

Benefits of technology

本发明提供了超级电容器外壳及具备其的超级电容器,本发明通过以下方法同时提高了超级电容器非金属外壳的耐电解液腐蚀性、抗冲击性和散热性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a supercapacitor shell and a supercapacitor with the same, and relates to the technical field of supercapacitors. The supercapacitor shell comprises the following raw materials in parts by mass: polyphenylene sulfide resin 65-70 parts, synergist 6-8 parts, and mixed heat-conducting filler 24-27 parts; wherein the synergist is polyether ether ketone micro powder modified by a silane coupling agent and chitin whisker; and the mixed heat-conducting filler is boron nitride nanosheet and nanoscale silicon carbide modified by a silane coupling agent after being pretreated by polyethylene glycol, ferrous sulfate heptahydrate and hydrogen peroxide. The supercapacitor preparation method comprises the following steps: placing a lower current collector, a negative electrode sheet, a diaphragm, a positive electrode sheet and an upper current collector into the inner cavity of the supercapacitor shell, then covering a cover, injecting an electrolyte, standing, sealing the liquid injection hole, leading out electrode leads, fixing the lead interfaces, and drying. The introduction of the synergist and other components effectively improves the electrolyte corrosion resistance and heat dissipation of the supercapacitor shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of supercapacitor technology, and more specifically to a supercapacitor casing and a supercapacitor having the same. Background Technology

[0002] Supercapacitors are a new type of energy storage device that falls between traditional physical capacitors and secondary batteries. They store energy based on double-layer capacitance or pseudocapacitance mechanisms, requiring no complex chemical reactions and completing charging and discharging solely through charge adsorption or rapid redox reactions. Their power density, charging and discharging speed, and cycle life are far superior to ordinary batteries. They are also adaptable to wide-temperature environments, emit no pollutants, and are highly safe. They have been widely applied in fields such as start-stop and regenerative braking for new energy vehicles, emergency power supply for electronic equipment, grid frequency regulation and peak compensation, and energy recovery in rail transit.

[0003] However, the non-metallic casings of supercapacitors still have the following performance shortcomings in practical applications: First, they lack resistance to electrolyte corrosion, and long-term contact with organic electrolytes can easily cause swelling and cracking, compromising sealing performance and leading to internal electrode oxidation failure. Second, they lack impact resistance, making them prone to casing deformation and cracking. Third, their heat dissipation performance is poor; the heat generated by rapid charge migration is difficult to dissipate efficiently through the non-metallic casing, leading to internal temperature accumulation, which reduces energy storage efficiency, accelerates material aging, and shortens the device's cycle life. Therefore, the electrolyte corrosion resistance, impact resistance, and heat dissipation performance of existing supercapacitor non-metallic casings still need to be improved. Summary of the Invention

[0004] The purpose of this invention is to provide a supercapacitor casing and a supercapacitor having the same, thereby solving the following technical problems: Existing supercapacitors with non-metallic casings still suffer from poor resistance to electrolyte corrosion, impact resistance, and heat dissipation.

[0005] The objective of this invention can be achieved through the following technical solutions: The supercapacitor casing comprises the following raw materials in parts by weight: 65-70 parts of polyphenylene sulfide resin, 6-8 parts of synergist, and 24-27 parts of mixed thermally conductive filler; The synergist is polyetheretherketone micro powder and chitin whiskers modified with silane coupling agent KH-560 at a pH of 4.0-4.5. The mixed thermally conductive filler is composed of boron nitride nanosheets and nano-silicon carbide modified with silane coupling agent KH-550 after being first dispersed in polyethylene glycol, then pretreated with ferrous sulfate heptahydrate and hydrogen peroxide.

[0006] Preferably, the synergist is prepared by the following method: Add polyetheretherketone (PEEK) micro powder to deionized water and stir for 20-30 min. Then, while stirring at 8000-10000 r / min, add chitin whisker suspension dropwise and stir for 1-1.5 h. Adjust the pH to 4.0-4.5 with 0.1 mol / L hydrochloric acid, add silane coupling agent KH-560 and stir for 60-70 min. Finally, centrifuge, vacuum dry at 45-50℃ for 12-16 h, and grind to obtain the synergist.

[0007] Preferably, the mass ratio of deionized water, polyetheretherketone micro powder, chitin whisker suspension, and silane coupling agent KH-560 is 100-120:1:1:0.2; The chitin whisker suspension has a mass fraction of 5%-10%.

[0008] Preferably, the preparation method of the mixed thermally conductive filler is as follows: A1: Add polyethylene glycol to deionized water and stir for 10-20 min. Then add boron nitride nanosheets and nano-silicon carbide and ultrasonically disperse for 60-80 min. Then adjust the pH to 2-3 and add ferrous sulfate heptahydrate. Stir for 20-30 min and then add hydrogen peroxide aqueous solution dropwise. Stir at 30-35℃ for 3-4 h. Then centrifuge and wash the precipitate with deionized water 5-7 times. Finally, vacuum dry at 60℃ for 8-10 h to obtain the pretreated mixed filler. A2: Add deionized water and glacial acetic acid to anhydrous ethanol and stir for 10-15 min. Then add silane coupling agent KH-550 and stir for 40-60 min. Next, add the pretreated mixed packing and stir and reflux at 70℃ for 4-6 h. Then centrifuge and wash with ethanol 3-5 times, then wash with deionized water 1-2 times alternately. Finally, vacuum dry at 80℃ for 12-15 h to obtain the mixed thermally conductive packing.

[0009] Preferably, the ratio of deionized water, polyethylene glycol, boron nitride nanosheets, nano-silicon carbide, ferrous sulfate heptahydrate, and hydrogen peroxide aqueous solution in A1 is 130-150mL: 0.3-0.5g: 30-40g: 2-4g: 0.2-0.4g: 5-7mL; The mass fraction of the hydrogen peroxide aqueous solution described in A1 is 30%.

[0010] Preferably, the ratio of anhydrous ethanol, deionized water, glacial acetic acid, silane coupling agent KH-550, and pretreated mixed filler in A2 is 150mL: 2-3g: 0.5-1g: 1.2-2g: 32-44g.

[0011] Preferably, the method for preparing the supercapacitor casing is as follows: S1: Mix polyphenylene sulfide resin, synergist, and mixed thermally conductive filler for 30-40 minutes, then perform melt extrusion treatment, followed by water cooling and pelletizing, and then drying at 120℃ for 5-7 hours to obtain composite masterbatch; S2: The composite masterbatch is injection molded, cooled, and then demolded to obtain the supercapacitor casing.

[0012] Preferably, the twin-screw extruder used in the melt extrusion process described in S1 has a length-to-diameter ratio of 40:1, a vacuum degree of -0.09 to 0.1 MPa, a zone 1 temperature of 290-295°C, a zone 2 temperature of 295-305°C, a zone 3 and 4 temperature of 300-310°C, a die temperature of 295°C, and a screw speed of 200-250 r / min.

[0013] Preferably, during the injection molding process described in S2, the barrel temperature is 290-310℃, the nozzle temperature is 305℃, the injection pressure is 80-100MPa, the holding pressure is 60-80MPa, and the mold temperature is 150-160℃.

[0014] A supercapacitor with a supercapacitor casing, the supercapacitor being manufactured as follows: The lower current collector, negative electrode, electrolyte-soaked diaphragm, positive electrode, and upper current collector are sequentially aligned and placed into the inner cavity of the supercapacitor casing. Then, the top cover with the injection hole is placed on top and electrolyte is injected through the injection hole. After standing for 30-50 minutes, the injection hole is sealed with epoxy resin. Then, the electrode leads are led out from the conductive terminal hole, and the lead interface is fixed with sealant. Finally, the supercapacitor is vacuum dried at 60-80℃ for 6-8 hours to obtain the supercapacitor.

[0015] The beneficial effects of this invention are: This invention provides a supercapacitor casing and a supercapacitor having the same. The invention simultaneously improves the electrolyte corrosion resistance, impact resistance, and heat dissipation of the non-metallic casing of the supercapacitor through the following methods.

[0016] (1) In the synergist of the present invention, polyether ether ketone and polyphenylene sulfide have similar chemical structures and excellent compatibility. The impact strength of polyether ether ketone itself is much higher than that of polyphenylene sulfide, which can directly fill the brittle defects of the polyphenylene sulfide matrix. After the chitin whiskers are dispersed, they can form a support network in the matrix, disperse the impact stress, and avoid fracture caused by stress concentration. The epoxy group of the silane coupling agent KH-560 can react with the active groups of polyether ether ketone, chitin whiskers and polyphenylene sulfide at the same time, strengthen the interfacial bonding force of the three phases, reduce the interfacial peeling during impact, further amplify the toughening effect and improve the impact resistance. Polyetheretherketone (PEEK) exhibits extremely strong chemical inertness and superior resistance to organic electrolytes and acid / alkali media compared to polyphenylene sulfide (PPS). It can form a protective layer on the surface of the PPS matrix, preventing electrolyte penetration. Chitosan whiskers have a stable molecular structure, making them less prone to reacting with commonly used electrolytes in supercapacitors. Furthermore, their nano-dispersion can fill the micropores in the matrix, reducing electrolyte intrusion channels. The interfacial bonding force enhanced by the silane coupling agent KH-560 can inhibit electrolyte penetration and erosion at the three-phase interface, preventing strength reduction caused by interfacial peeling after long-term immersion and improving impact strength retention.

[0017] (2) In this invention, both boron nitride nanosheets and nano-silicon carbide are highly thermally conductive insulating fillers, which can form a continuous thermally conductive network after being combined. The ultrasonic dispersion process reduces filler agglomeration, and the modification with silane coupling agent KH-550 reduces the interfacial thermal resistance between the filler and the polyphenylene sulfide matrix, allowing for smoother heat transfer and thus significantly improving the thermal conductivity of the shell. Boron nitride nanosheets and nano-silicon carbide have extremely strong chemical stability and are resistant to corrosion from commonly used electrolytes in supercapacitors, such as organic electrolytes and ionic liquids, and will not react with the electrolyte. The modification with silane coupling agent KH-550 strengthens the interfacial bonding between boron nitride nanosheets, nano-silicon carbide and the polyphenylene sulfide matrix, reduces the channels for electrolyte penetration into the interface, and avoids structural damage caused by interfacial peeling. At the same time, polyphenylene sulfide itself has excellent chemical corrosion resistance, and its corrosion resistance is further improved after being combined with stable inorganic fillers.

[0018] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. The embodiments described below are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] Unless otherwise specified, the following information pertains to some of the raw materials used in the following embodiments and comparative examples of this invention: The polyetheretherketone micro powder was purchased from Shanghai Jieshikai Biotechnology Co., Ltd., item number: KA679524-100g; the polyphenylene sulfide resin was purchased from Airefu (Shanghai) New Material Technology Co., Ltd., item number: FORTRON 1200L1.

[0021] Example 1: The supercapacitor casing and the method for manufacturing a supercapacitor containing the casing are as follows: S1: Add 1g of polyetheretherketone micro powder to 100mL of deionized water and stir for 20min. Then, while stirring at 8000r / min, add 1g of 5% chitin whisker suspension dropwise and stir for 1h. Adjust the pH to 4 with 0.1mol / L hydrochloric acid, add 0.2g of silane coupling agent KH-560 and stir for 60min. Finally, centrifuge, vacuum dry at 45℃ for 12h, and grind to obtain the synergist. S2: Add 0.3g polyethylene glycol to 130mL of deionized water and stir for 10min. Then add 30g boron nitride nanosheets and 2g silicon carbide nanosheets and ultrasonically disperse for 60min. Then adjust the pH to 2 and add 0.2g ferrous sulfate heptahydrate. Stir for 20min and then add 5mL of 30% hydrogen peroxide aqueous solution. Stir at 30℃ for 3h. Then centrifuge and wash the precipitate 5 times with deionized water. Finally, vacuum dry at 60℃ for 8h to obtain the pretreated mixed filler. S3: Add 2g of deionized water and 0.5g of glacial acetic acid to 150mL of anhydrous ethanol and stir for 10min. Then add 1.2g of silane coupling agent KH-550 and stir for 40min. Then add 32g of pretreated mixed packing and stir and reflux at 70℃ for 4h. Then centrifuge and wash with ethanol 3 times, then wash with deionized water once alternately. Then vacuum dry at 80℃ for 12h to obtain mixed thermally conductive packing. S4: Mix 65g of polyphenylene sulfide resin, 6g of synergist, and 24g of mixed thermally conductive filler for 30 minutes. Then, melt extrude the mixture in a twin-screw extruder with a length-to-diameter ratio of 40:1 at a vacuum of -0.09MPa, a zone 1 temperature of 290℃, a zone 2 temperature of 295℃, a zone 3 and zone 4 temperature of 300℃, a die temperature of 295℃, and a screw speed of 200r / min. After water cooling and pelletizing, the mixture is dried at 120℃ for 5 hours to obtain the composite masterbatch. S5: The composite masterbatch is subjected to injection molding at a barrel temperature of 290℃, a nozzle temperature of 305℃, an injection pressure of 80MPa, a holding pressure of 60MPa, and a mold temperature of 150℃. After holding pressure and cooling, it is demolded to obtain the supercapacitor shell. S6: Place the lower current collector, negative electrode, electrolyte-soaked diaphragm, positive electrode, and upper current collector into the inner cavity of the supercapacitor housing in sequence. Then, cover the top cover with the injection hole and inject electrolyte through the injection hole. After standing for 30 minutes, seal the injection hole with epoxy resin. Then, lead out the electrode leads from the conductive terminal holes and fix the lead interface with sealant. Finally, vacuum dry at 60°C for 6 hours to obtain the supercapacitor.

[0022] Example 2: The supercapacitor casing and the method for preparing a supercapacitor containing the casing are as follows: S1: Add 1g of polyetheretherketone micro powder to 110mL of deionized water and stir for 25min. Then, while stirring at 9000r / min, add 1g of chitin whisker suspension with a mass fraction of 8% and stir for 1.2h. Adjust the pH to 4.3 with 0.1mol / L hydrochloric acid, add 0.2g of silane coupling agent KH-560 and stir for 65min. Finally, centrifuge, vacuum dry at 48℃ for 14h, and grind to obtain the synergist. S2: Add 0.4g polyethylene glycol to 140mL of deionized water and stir for 15min. Then add 35g boron nitride nanosheets and 3g silicon carbide nanosheets and ultrasonically disperse for 70min. Then adjust the pH to 2.5 and add 0.3g ferrous sulfate heptahydrate. Stir for 25min and then add 6mL of 30% hydrogen peroxide aqueous solution. Stir at 33℃ for 3.5h. Then centrifuge and wash the precipitate 6 times with deionized water. Finally, vacuum dry at 60℃ for 9h to obtain the pretreated mixed filler. S3: Add 2.5g of deionized water and 0.8g of glacial acetic acid to 150mL of anhydrous ethanol and stir for 13min. Then add 1.6g of silane coupling agent KH-550 and stir for 50min. Then add 38g of pretreated mixed packing and stir and reflux at 70℃ for 5h. Then centrifuge and wash with ethanol 4 times, then wash with deionized water once alternately. Then vacuum dry at 80℃ for 14h to obtain mixed thermally conductive packing. S4: Mix 67.5g of polyphenylene sulfide resin, 7g of synergist, and 25.5g of mixed thermally conductive filler for 35 minutes. Then, melt extrude the mixture in a twin-screw extruder with a length-to-diameter ratio of 40:1 at a vacuum of -0.1MPa, a zone 1 temperature of 293℃, a zone 2 temperature of 300℃, a zone 3 and 4 temperature of 305℃, a die temperature of 295℃, and a screw speed of 230r / min. After water cooling and pelletizing, the mixture is dried at 120℃ for 6 hours to obtain the composite masterbatch. S5: The composite masterbatch is subjected to injection molding at a barrel temperature of 300℃, a nozzle temperature of 305℃, an injection pressure of 90MPa, a holding pressure of 70MPa, and a mold temperature of 155℃. After holding pressure and cooling, it is demolded to obtain the supercapacitor shell. S6: Place the lower current collector, negative electrode, electrolyte-soaked diaphragm, positive electrode, and upper current collector into the inner cavity of the supercapacitor housing in sequence. Then, cover the top cover with the injection hole and inject electrolyte through the injection hole. After standing for 40 minutes, seal the injection hole with epoxy resin. Then, lead out the electrode leads from the conductive terminal holes and fix the lead interface with sealant. Finally, vacuum dry at 70°C for 7 hours to obtain the supercapacitor.

[0023] Example 3: The supercapacitor casing and the method for manufacturing a supercapacitor containing the casing are as follows: S1: Add 1g of polyetheretherketone micro powder to 120mL of deionized water and stir for 30min. Then, while stirring at 10000r / min, add 1g of chitin whisker suspension with a mass fraction of 10% and stir for 1.5h. Adjust the pH to 4.5 with 0.1mol / L hydrochloric acid, add 0.2g of silane coupling agent KH-560 and stir for 70min. Finally, centrifuge, vacuum dry at 50℃ for 16h, and grind to obtain the synergist. S2: Add 0.5g polyethylene glycol to 150mL of deionized water and stir for 20min. Then add 40g boron nitride nanosheets and 4g silicon carbide nanosheets and ultrasonically disperse for 80min. Then adjust the pH to 3 and add 0.4g ferrous sulfate heptahydrate. Stir for 30min and then add 7mL of 30% hydrogen peroxide aqueous solution. Stir at 35℃ for 4h. Then centrifuge and wash the precipitate 7 times with deionized water. Finally, vacuum dry at 60℃ for 10h to obtain the pretreated mixed filler. S3: Add 3g of deionized water and 1g of glacial acetic acid to 150mL of anhydrous ethanol and stir for 15min. Then add 2g of silane coupling agent KH-550 and stir for 60min. Then add 44g of pretreated mixed packing and stir and reflux at 70℃ for 6h. Then centrifuge and wash with ethanol 5 times, then wash with deionized water twice alternately. Then vacuum dry at 80℃ for 15h to obtain mixed thermally conductive packing. S4: Mix 70g of polyphenylene sulfide resin, 8g of synergist, and 27g of mixed thermally conductive filler for 40 minutes. Then, melt extrude the mixture in a twin-screw extruder with a length-to-diameter ratio of 40:1 at a vacuum of -0.1MPa, a zone 1 temperature of 295℃, a zone 2 temperature of 305℃, a zone 3 and zone 4 temperature of 310℃, a die temperature of 295℃, and a screw speed of 250r / min. After water cooling and pelletizing, the mixture is dried at 120℃ for 7 hours to obtain the composite masterbatch. S5: The composite masterbatch is subjected to injection molding at a barrel temperature of 310℃, a nozzle temperature of 305℃, an injection pressure of 100MPa, a holding pressure of 80MPa, and a mold temperature of 160℃. After holding pressure and cooling, it is demolded to obtain the supercapacitor shell. S6: Place the lower current collector, negative electrode, electrolyte-soaked diaphragm, positive electrode, and upper current collector into the inner cavity of the supercapacitor housing in sequence. Then, cover the top cover with the injection hole and inject electrolyte through the injection hole. After standing for 50 minutes, seal the injection hole with epoxy resin. Then, lead out the electrode leads from the conductive terminal holes and fix the lead interface with sealant. Finally, vacuum dry at 80°C for 8 hours to obtain the supercapacitor.

[0024] Comparative Example 1: Compared with Example 1, this comparative example only did not add "polyether ether ketone micro powder" in the preparation process of S1. All other steps and parameters are the same, and will not be repeated here. Finally, a supercapacitor shell and a supercapacitor with it are obtained.

[0025] Comparative Example 2: Compared with Example 1, this comparative example only did not add a "synergist" in the preparation process of S4. All other steps and parameters were the same, and will not be repeated here. The final result is a supercapacitor shell and a supercapacitor with the shell.

[0026] Comparative Example 3: Compared with Example 1, this comparative example only omits the addition of "mixed thermally conductive filler" in the preparation process of S4. All other steps and parameters are the same, and will not be repeated here. The final result is a supercapacitor shell and a supercapacitor containing it.

[0027] Performance testing: Impact resistance testing: Referring to GB / T 1043.1-2008 standard, the unnotched impact strength (kJ / m²) of the simply supported beam of the supercapacitor shells prepared in Examples 1-3 and Comparative Examples 1-3 of this invention was measured. 2 The test results are shown in Table 1. Insulation determination: The insulation resistance (Ω) of the supercapacitor shells prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention was measured according to GB / T 10064-2006 standard. The test results are shown in Table 1. Measurement of thermal conductivity: Referring to GB / T 42919.6-2023 standard, the thermal conductivity (W·m) of the supercapacitor shells prepared in Examples 1-3 and Comparative Examples 1-3 of this invention was measured. -1 ·K -1 The test results are shown in Table 1. Corrosion resistance testing: Referring to GB / T 1043.1-2008 standard, the impact strength retention rate (%) of the supercapacitor shells prepared in Examples 1-3 and Comparative Examples 1-3 of this invention after immersion in a 1 mol / L lithium hexafluorophosphate (solute) + dimethyl carbonate electrolyte (solvent) at 60°C for 1000 h was determined. The test results are shown in Table 1. Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-3

[0028] Data Analysis: As can be seen from Table 1, the supercapacitor shell prepared in the embodiments of the present invention has excellent impact resistance, insulation, thermal conductivity and corrosion resistance.

[0029] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A supercapacitor casing, characterized in that, The raw materials include the following parts by weight: 65-70 parts of polyphenylene sulfide resin, 6-8 parts of synergist, and 24-27 parts of mixed thermally conductive filler; The synergist is polyetheretherketone micro powder and chitin whiskers modified with silane coupling agent KH-560 at a pH of 4.0-4.

5. The mixed thermally conductive filler is composed of boron nitride nanosheets and nano-silicon carbide modified with silane coupling agent KH-550 after being first dispersed in polyethylene glycol, then pretreated with ferrous sulfate heptahydrate and hydrogen peroxide.

2. The supercapacitor casing according to claim 1, characterized in that, The preparation method of the synergist is as follows: Add polyetheretherketone micro powder to deionized water and stir for 20-30 minutes. Then add chitin whisker suspension dropwise and stir for 1-1.5 hours. Adjust the pH to 4-4.5, add silane coupling agent KH-560 and stir for 60-70 minutes. Finally, centrifuge, dry and grind to obtain the synergist.

3. The supercapacitor casing according to claim 2, characterized in that, The mass ratio of deionized water, polyetheretherketone micro powder, chitin whisker suspension, and silane coupling agent KH-560 is 100-120:1:1:0.

2. The chitin whisker suspension has a mass fraction of 5%-10%.

4. The supercapacitor casing according to claim 1, characterized in that, The preparation method of the mixed thermally conductive filler is as follows: A1: Add polyethylene glycol to deionized water and stir for 10-20 min. Then add boron nitride nanosheets and nano-silicon carbide and ultrasonically disperse for 60-80 min. Then adjust the pH to 2-3 and add ferrous sulfate heptahydrate. Stir for 20-30 min and then add hydrogen peroxide aqueous solution dropwise. Stir at 30-35℃ for 3-4 h. Then centrifuge, wash and dry to obtain the pretreated mixed packing. A2: Add deionized water and glacial acetic acid to anhydrous ethanol and stir for 10-15 min. Then add silane coupling agent KH-550 and stir for 40-60 min. Subsequently, add pretreated mixed packing and stir and reflux at 70℃ for 4-6 h. Then centrifuge, wash and dry to obtain mixed thermally conductive packing.

5. The supercapacitor casing according to claim 4, characterized in that, The ratio of deionized water, polyethylene glycol, boron nitride nanosheets, nano-silicon carbide, ferrous sulfate heptahydrate, and hydrogen peroxide aqueous solution described in A1 is 130-150mL: 0.3-0.5g: 30-40g: 2-4g: 0.2-0.4g: 5-7mL; The mass fraction of the hydrogen peroxide aqueous solution described in A1 is 30%.

6. The supercapacitor casing according to claim 4, characterized in that, The ratio of anhydrous ethanol, deionized water, glacial acetic acid, silane coupling agent KH-550, and pretreated mixed packing material in A2 is 150mL: 2-3g: 0.5-1g: 1.2-2g: 32-44g.

7. The supercapacitor casing according to claim 1, characterized in that, The method for preparing the supercapacitor casing is as follows: S1: Mix polyphenylene sulfide resin, synergist, and mixed thermally conductive filler for 30-40 minutes, then perform melt extrusion treatment, followed by water cooling, pelletizing, and drying to obtain composite masterbatch; S2: The composite masterbatch is injection molded, cooled, and then demolded to obtain the supercapacitor casing.

8. The supercapacitor casing according to claim 7, characterized in that, The twin-screw extruder used in the melt extrusion process described in S1 has a length-to-diameter ratio of 40:1, a vacuum degree of -0.09 to 0.1 MPa, a zone 1 temperature of 290-295℃, a zone 2 temperature of 295-305℃, a zone 3 and 4 temperature of 300-310℃, a die temperature of 295℃, and a screw speed of 200-250 r / min.

9. The supercapacitor casing according to claim 7, characterized in that, In S2, the injection molding process involves a barrel temperature of 290-310℃, a nozzle temperature of 305℃, an injection pressure of 80-100MPa, a holding pressure of 60-80MPa, and a mold temperature of 150-160℃.

10. A supercapacitor with a supercapacitor casing according to any one of claims 1-9, characterized in that, The supercapacitor is prepared as follows: The lower current collector, negative electrode, electrolyte-soaked diaphragm, positive electrode, and upper current collector are sequentially aligned and placed into the inner cavity of the supercapacitor casing. Then, the top cover with the injection hole is placed on top and electrolyte is injected through the injection hole. After standing for 30-50 minutes, the injection hole is sealed with epoxy resin. Then, the electrode leads are led out from the conductive terminal hole, and the lead interface is fixed with sealant. Finally, the supercapacitor is vacuum dried at 60-80℃ for 6-8 hours to obtain the supercapacitor.